Attitudinal Shifts Regarding Gender Segregation Among Saudi Males: The influence of Overseas Study Experiences (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study aimed at investigating the divergence in attitudes between Saudi students who have lived in the United States for four years or more compared to Saudi students who have not lived outside Saudi Arabia for more than a three-month period. A survey was designed based on the main aspects of Saudi culture for this study as surveys are found to be the most common means for measuring attitudes. Two samples of Saudi students were recruited, one sample included students who have lived in the United States for four years or more, and the other sample consisted of those who have not lived outside Saudi Arabia for more than three months. A statistically significant difference between the two samples was found; students who have lived in the United States for four years or more were found to be more tolerant than those who have not lived abroad for more than three months towards the issue of sex segregation in mixed environments.